2016
DOI: 10.1590/1678-69712016/administracao.v17n6p134-163
|View full text |Cite
|
Sign up to set email alerts
|

Scaling up social innovation: a meta-synthesis

Abstract: Purpose:This paper aims to analyze how features raised in the case studies in the field of social innovation, from the meta-synthesis methodology proposed by Hoon (2013), indicate factors that promote social innovation scalability Originality/gap/relevance/implications: The number of publications on SI, despite an increase perceived, is still limited. Consequently, researches dedicated to understand the scalability of the process of SI are still scarce, thus constituting a gap research. Key methodological aspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 64 publications
1
17
0
5
Order By: Relevance
“…The organizational learning is considered an important element in the successful cases of diffusion of the SI (Voltan and De Fuentes, 2016). It happens when the SE creates new knowledge based on the lessons learned from previous experiences, when it adjusts to environmental changes and offers training to promote internal development (Morais-da-Silva et al, 2016;Mulyaningsih et al, 2014).…”
Section: An Integrated Framework Of Social Innovation Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…The organizational learning is considered an important element in the successful cases of diffusion of the SI (Voltan and De Fuentes, 2016). It happens when the SE creates new knowledge based on the lessons learned from previous experiences, when it adjusts to environmental changes and offers training to promote internal development (Morais-da-Silva et al, 2016;Mulyaningsih et al, 2014).…”
Section: An Integrated Framework Of Social Innovation Managementmentioning
confidence: 99%
“…However, it is worth pointing out Culture. A proper environment for the creation of SI involves a process of co-building and sharing knowledge between all involved (internal and external) (Vezina et al, 2019), a willingness to improve social well-being that is greater than the fear of failure, strong levels of intrapreneurship and less dependence on a leader that only encourages innovation inwards (Berzin and Pitt-Catsouphes, 2015;Biggeri et al, 2017;Martins et al, 2020;Morais-da-Silva et al, 2016;Pasricha and Rao, 2018;Quandt et al, 2017). For example, when analysing the SI process in a large SE, Altuna et al, (2015) found that the ability to shape societal demand into a new product / service involves a decentralized process of product definition by the Finally, according to Dufays (2019), team members seem further motivated to simultaneously embrace both the social and the commercial dimensions needed for implementation of SI when they have both a mutual interest at stake and a general interest (superimposition of the producer/investor role with the beneficiary role).…”
Section: An Integrated Framework Of Social Innovation Managementmentioning
confidence: 99%
“…Social Innovation refers to new solutions that seek to improve living conditions of groups excluded and meet their social needs in a more effective way than current solutions; at the same time that it increases the capabilities, relationships and process of societies (Murray et al, 2010;Cajaiba-Santana, 2014;Morais-Da-Silva, 2016). Under this definition, social innovation must include something novel in the satisfaction of some social need; it could be incremental or disruptive and in it has to be more effective and efficient.…”
Section: Social Innovation and Social Enterprises: An Alternative To mentioning
confidence: 99%
“…Social innovations can take several forms in their implementation, such as new products, services, platforms or organizational forms; and they are not particular of any sector of the economy, they can emerge in non-profit, private, public organizations, or even the informal sector (Caulier-Grice, Davies, Patrick & Norman, 2012). Most social innovations integrate actors from different sectors to increase their impact and scalability, which is one of the main features of social innovation (Westley & Antadze, 2010;Portales, 2015;Le Pennec & Raufflet, 2016;Morais-Da-Silva, 2016). Additionally, to the social innovations created by private and social sectors, social enterprises have emerged as a new type of social innovation and that now constitute a new sector.…”
Section: Social Innovation and Social Enterprises: An Alternative To mentioning
confidence: 99%
“…Antes de abordar a inovação social em grandes corporações, pretende-se abordar o conceito mais amplo de inovação social. O termo inovação social tem recebido crescente atenção de acadêmicos e da sociedade civil em especial na última década, mas a literatura sobre o assunto permanece pouco desenvolvida, caracterizando-se como um campo de conhecimento ainda fragmentado e não consolidado, dado seu caráter multidisciplinar e a ênfase geralmente atribuída a inovações tecnológicas em geral (Bignetti, 2011;Cajaiba-Santana, 2014;Comini, 2016;Morais-da-Silva, Takahashi, & Segatto, 2016;Moulaert, Maccallum, Mehmood, & Hamdouch, 2013;Pol & Ville, 2009).…”
Section: Inovação Socialunclassified